Studies on the Biodiversity of Halophilic Microorganisms Isolated from El-Djerid Salt Lake (Tunisia) under Aerobic Conditions. (30th November 2009) - Hedi, Abdeljabbar; Sadfi, Najla; Fardeau, Marie-Laure; Rebib, Hanene; Cayol, Jean-Luc; Ollivier, Bernard; Boudabous, Abdellatif
Abstract : Bacterial and archaeal aerobic communities were recovered from sediments from the shallow El-Djerid salt lake in Tunisia, and their salinity gradient distribution was established. Six samples for physicochemical and microbiological analyses were obtained from 6 saline sites in the lake for physico-chemical and microbiological analyses. All samples studied were considered hypersaline with NaCl concentration ranging from 150 to 260 g/L. A specific halophilic microbial community was recovered from each site, and characterization of isolated microorganisms was performed via both phenotypic and phylogenetic approaches. Only one extreme halophilic organism, domain Archaea, was isolated from site 4 only, whereas organisms in the domain Bacteria were recovered from the five remaining sampling sites that contained up to 250 g/L NaCl. Members of the domain Bacteria belonged to genera Salicola, Pontibacillus, Halomonas, Marinococcus, and Halobacillus, whereas the only member of domain Archaea isolated belonged to the genus Halorubrum . The results of this study are discussed in terms of the ecological significance of these microorganisms in the breakdown of organic matter in Lake El-Djerid and their potential for industry applications.